WORKSHOP DESAIN GRAFIS UNTUK MENINGKATKAN IDENTITAS UMKM - Andri Nata; Febby Madonna Yuma; Iin Almeina Lubis (Smart Education, 2024)
Abstract: The Graphic Design Workshop to Enhance SME Identity is an initiative aimed at empowering micro, small, and medium enterprises through the strengthening of their visual identity. In today's competitive digital era, a strong and consistent visual identity is a key factor in attracting customers' attention and building a trustworthy brand. This workshop is designed to provide intensive training to SME practitioners on the basic principles of graphic design, the use of design software, and effective visual identity development strategies. Through a practical and interactive approach, participants will learn how to create logos, product packaging, promotional materials, and engaging, professional social media content. The expected outcome of this workshop is an improvement in participants' graphic design skills that can be directly applied to their businesses, thereby increasing competitiveness and market visibility. Evaluation of the workshop shows that participants experience significant improvements in design skills and understanding of the importance of a strong visual identity for business growth. This workshop demonstrates that with the right support and training, SMEs can leverage graphic design to build a unique and captivating identity, ultimately contributing to the success of their businesses. Keywords: Graphic Design; Logo; UMKM; Abstrak: Workshop Desain Grafis untuk Meningkatkan Identitas UMKM adalah sebuah inisiatif yang bertujuan untuk memberdayakan usaha mikro, kecil, dan menengah (UMKM) melalui penguatan identitas visual mereka. Dalam era digital yang kompetitif ini, identitas visual yang kuat dan konsisten menjadi faktor kunci untuk menarik perhatian pelanggan dan membangun brand yang terpercaya. Workshop ini dirancang untuk memberikan pelatihan intensif kepada pelaku UMKM tentang prinsip-prinsip dasar desain grafis, penggunaan perangkat lunak desain, dan strategi pengembangan identitas visual yang efektif. Melalui pendekatan praktis dan interaktif, peserta akan belajar cara membuat logo, kemasan produk, materi promosi, serta konten media sosial yang menarik dan profesional. Hasil yang diharapkan dari workshop ini adalah peningkatan kemampuan desain grafis peserta yang dapat diterapkan langsung pada usaha mereka, sehingga meningkatkan daya saing dan visibilitas di pasar. Evaluasi dari workshop menunjukkan bahwa peserta mengalami peningkatan signifikan dalam keterampilan desain dan pemahaman tentang pentingnya identitas visual yang kuat untuk pertumbuhan bisnis. Workshop ini membuktikan bahwa dengan dukungan dan pelatihan yang tepat, UMKM dapat memanfaatkan desain grafis untuk membangun identitas yang unik dan memikat, yang pada akhirnya berkontribusi pada keberhasilan usaha mereka. Kata kunci: Desain Grafis; Logo; UMKM;